2021
DOI: 10.1002/aelm.202100905
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Operating‐Voltage Resistive Switching Memory Based on the Interlayer‐Spacing Regulation of MoSe2

Abstract: The development of commercially available flexible and wearable devices requires low‐operating‐voltage circuit and resistive random access memory (RRAM). This paper reports the preparation and performances of low‐operating‐voltage RRAM based on the interlayer‐spacing regulation of MoSe2. Twine‐jumble‐like MoSe2 clusters were synthesized via hydrothermal method. The average interlayer spacing in the clusters is higher than the value for bulk MoSe2 by 9.969%. The layer count of the MoSe2 sample predicted accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The lattice distortion δ can be calculated according to eqs S2, S4 and S5. Concerning the reported SET voltages and the calculated values of δ for TMDs, as shown in Figure a, it is found that δ/ d ( d is the spacing between the two S atom layers, while δ denotes the interlayer spacing variation for forming the Ag conductive filament) increases linearly with increasing V SET . When V SET is equal to 0.31 V, δ is decreased to 0.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The lattice distortion δ can be calculated according to eqs S2, S4 and S5. Concerning the reported SET voltages and the calculated values of δ for TMDs, as shown in Figure a, it is found that δ/ d ( d is the spacing between the two S atom layers, while δ denotes the interlayer spacing variation for forming the Ag conductive filament) increases linearly with increasing V SET . When V SET is equal to 0.31 V, δ is decreased to 0.…”
Section: Resultsmentioning
confidence: 93%
“…According to the vdW interlayer spacing determined by experiments, the values of r g for SnS 2 nanosheets, SnS 2 flower-like microspheres (Figure S4), MoS 2 flower-like microspheres (Figure S5), MoS 2 thin films, MoSe 2 flower-like microspheres, MoSe 2 nanorods and WS 2 nanosheets with wide vdW interlayer spacings and those for bulk SnS 2 , MoS 2 , MoSe 2 and WS 2 with normal vdW interlayer spacings were calculated by using eq . Table S1 lists the calculated values of r g , while Table lists the SET voltage, SET power, switching ratio, and endurance of TMD-based RRAMs with different values of r g .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations